Cold housing: evidence, risk and vulnerability. Issue 1 (2nd January 2021) - Daniel, Lyrian; Baker, Emma; Beer, Andrew; Pham, Ngoc Thien Anh
Abstract: Cold housing is not widely recognized as a problem that occurs in mild-climate countries like Australia. But emerging evidence suggests that it is an important, albeit under-acknowledged, problem that may contribute to high rates of ill health and mortality during the winter months. We bring together two historically important theoretical developments to better understand the social and economic distribution of cold housing. Drawing on nationally representative data from the Household, Income and Labour Dynamics in Australia survey between 2001 and 2016, we find that the characteristics of households unable to adequately heat their homes strongly reflects known patterns of inequality across, for example, tenure, employment and health, but that there are also more unexpected trends in age and income. Critically, our analyses demonstrate that individuals' vulnerability to cold housing risk can be anticipated, which has important implications for public policy and community-based interventions.